EFFECT OF EXTRACTING METHOD OF COCONUT OILS ON TRIBOLOGICAL PROPERTIES AS BIO-BASED LUBRICANT - Gasni, Dedison; Mulyadi, Ismet Hari (Journal of Applied Engineering Science, 2022)
The use of mineral and synthetic lubricants will have long-term impact on the environment. Vegetable oil can be an alternative for substitution due to having significant environmental benefits. In addition, vegetable oils also offer renewable resources and have proven to have excellent lubrication performance for automotive and industrial application. Coconut oil is one of vegetable-based oil that would have prospective characteristics to be exploited as bio-lubricant oil. The origin of coconut oil would distinguish its characteristic, hence differentiating its performance as a lubricant. Indonesia is well known as having abundant source of coconut oil which is made with different extraction methods. Extraction method can be envisaged for improving the performance of coconut oil as lubricant oil. Indonesian coconut oils that had been extracted through dry and wet methods would be a primary concern in this study. The prospective of extracting method of coconut oil as lubricant in term of physicochemical and tribological properties will be investigated. hydrogenated coconut oil (HCO), virgin coconut oil (VCO), and refined coconut oil (RCO) are product of coconut oil extracted from wet and dry, respectively. Results indicated that RCO and HCO posed high viscosity index, high ratio unsaturated to saturated fatty acids, and low wear and friction coefficient which are prospective as base fluid in lubricant industries.